Endovascular stroke treatment’s impact on malignant type of edema (ESTIMATE) - Fuhrer, Hannah; Schönenberger, Silvia; Seide, Svenja; Möhlenbruch, Markus Alfred; Kieser, Meinhard; Ringleb, Peter A. (Journal of neurology, 2019)
Background and purposeIn patients with acute ischemic stroke and large vessel occlusion, the prognosis has improved tremendously since the implementation of endovascular thrombectomy (EVT). The effect of EVT on the incidence of malignant middle cerebral artery infarctions (MMI) has not been studied before.MethodsESTIMATE, a multicenter retrospective study, evaluates data of ischemic stroke patients with occlusion in the anterior circulation in the years of 2007-2015 comparing three treatment options (no therapy; IV-TPA; IV-TPA plus EVT or EVT only). Primary endpoint of the study was the incidence of MMI on follow-up imaging and mortality rates. Secondary endpoints were functional outcome, further clinical and imaging data. Logistic and Cox-regression models with a propensity score weighting approach were applied to evaluate differences between treatment groups.ResultsIn 2161 patients over 9 years, EVT reduced the MMI rates significantly: patients without acute stroke treatment had increased odds for MMI of 1.57 [95% confidence interval (CI) 1.49-1.65]. In contrast, after treatment with IV-TPA, only we observed an OR of 0.88 (95% CI 0.83-0.94, p < 0.001), and after EVT an OR of 0.80 (95% CI 0.76-0.85, p < 0.001). This was more pronounced in larger pretreatment infarctions (ASPECTS < 5, p < 0.01). IV-TPA also lowers the MMI rates but not to the same extent. EVT-treated patients had increased survival rates (p < 0.05) and the best functional outcome at discharge.ConclusionsThe findings of this study illustrate that occurrence of MMI and mortality rates was significantly reduced in patients treated with EVT.
Published online: 23 November 2018
Gesehen am 11.07.2019